Living with nature and things: contributions to a new social history of the middle Islamic periods - Walker, Bethany J.; Al Ghouz, Abdelkader (Mamluk studies, 2020)
Angaben zur beteiligten Person Walker: Prof Dr Bethany J. Walker is Research Professor of Mamluk Studies at the University of Bonn and Director of the Research Unit of Islamic Archaeology. A historically-trained archaeologist, she directs several field projects in Jordan and Israel.
Keywords: 1258-1517; Islamic Empire -- History -- 1258-1517 -- Congresses; Islamic Empire -- Social conditions -- Congresses; Islamic Empire -- Antiquities -- Congresses; Empire islamique - Histoire - 1258-1517 - Congrès; Empire islamique - Conditions sociales - Congrès; Islamic Empire; Islamic Empire - History - 1258-1517 - Congresses; Islamic Empire - Social conditions - Congresses; Islamic Empire - Antiquities - Congresses; Congress; Konferenzschrift -- Annemarie Schimmel Kolleg -- 05.-07.12.2016 -- Bonn; Sachkultur; Umweltbewusstsein; Pest; Geschichte 969-1400; Landschaftsschaden; Wassernutzung; Umweltnutzung; Stadt; Osmanisches Reich; Mameluckenreich; Geschichte 800-1500; Mäzenatentum